OBSTACLE EXECUTION DECISION COURT TAX AS CONSEQUENCE FINDINGS WRONG WRITING / MISCOUNTING IN THE RELATIONSHIP WITH MANDATORY LEGAL CERTAINTY TAX - Ramadani Yunus; Khalimi; Sartono; Yuhelson; Ramlani Lina Sinaulan (Scholar Express Journals, 2022)
Court tax is court level first and level final in settlement ataas dispute tax , because that decision court taxes that have inkracht Becomes decision end have strength law stay . Constitution Number 14 of 2002 concerning court tax state that decision court tax live could implemented with no need again decision authorized official except regulation legislation another set however in implementation execution applicant execution in matter this must tax experience one of the obstacles ie found a typo or miscalculated in decision so that matter the Becomes obstacle in implementation execution. Therefore interesting for done study juridical related how action Director General Tax to decision court taxes that have been miswritten / miscalculated so that Becomes obstacle to execution decision court tax as well as certainty law for must tax to decision court tax included There is a typo / miscalculation Method The method used in this research is juridical law research method - focused normative approach regulation legislation ( statute approach ) and approach analysis ( analytical approach ) . Studies conducted use theory certainty law , theory justice law as well as theory related with execution on implementation something decision court . From the results of research could concluded that actions taken by the Director General Taxes on decisions contained therein There is a typo / miscalculation that is make report results study on decision then made base as application rectification intended decision to Court Tax and Director General Tax postpone implementation execution until exists rectification decision accepted. Certainty law for must tax Becomes delayed because decision decision the no have strength executive . As for the suggestion in this study is the panel of judges in check a case in court should more thorough and observant to the decision he made supported with inspection maximum concept by clerks replacement . For rectification decision should no must submit application inspection quick trial to court tax as Circular Letter Director General Tax No. SE-41/PJ/2014 Concerning Handling and Implementation Procedures Appeals Judgment, Judgment Lawsuit and Judgment Reconsideration, for ensure certainty law for must tax
Keywords: Obstacle Execution; Judgment Court Tax; Writing Mistake; Count